Correlation of Angiographic Scoring System with Percutaneous Revascularization Success in Chronic Coronary Total Occlusion Patients - Balghith, Mohammed A.; Alharbi, Ibrahim S.; Anezi, Abdurrahman S. Al (Cardiology and Cardiovascular Medicine, 2020)
Background: The percutaneous coronary intervention of chronic total occlusions (CTOs) is considered the most challenging technical procedure in the current interventional cardiology. Japanese Multicenter CTO Registry (J-CTO Score) was established to predict the probability of successful guidewire crossing through a half-hour. Aim: To assess the correlation of J score with percutaneous revascularization success in chronic coronary total occlusion patients. Method: This is a retrospective study that was included CTO patients who underwent coronary angiography at Cardiac Catheterization Laboratory at King Abdul-Aziz Cardiac Center between January 2010 - December 2017 will be extracted from an electronic database ( Apollo Lx, Best Care, Xcelera, Muse). Data collected from patients included demographics, cardiovascular risk factors, comorbidities, angiographic parameters, Haemodynamic Measurements, and laboratory tests. SPSS was used to analyze data. Results: There were 173 patients included in the study, the mean±SD of CTOs number was1.4±0.8, the mean±SD of J-CTO score was1.8±0.9, the mean ±SD of fluro time was 29.3±14. There was no significant association between J-CTO score and outcome of patients (P=0.6), the amount of contrast used also had no significant association with patients‘outcome (P=0.4), whereas the mean of fluro time was significantly associated with outcome of patients (P=0.01). Conclusion: J score showed no association with the success rate, however lower fluro time was a predictor of success